현재의 국내 응급의료체계에서 중증외상환자의 이송 지연 - 정경원; 장정문; 김지영; 백숙자; 송서영; 강찬숙; 이국종 (Daehan oe'sang haghoeji, 2011)
Purpose: Major trauma patients should be transferred to a definitive care facility as early as possible because prompt management will prevent death. This study was designed to discover the obstacles leading to delayed transfers under the current emergency medical system in Korea and whether there are any negative outcomes associated with conducting procedures at primary care hospitals prior to transferring patients to higher levels of care. Methods: The medical records of major trauma patients with an Injury Severity Score above 15 within the past year were reviewed. Patients were divided three groups as follows: (A) came directly to our emergency center, (B) were transferred without CT or MRI scan at the primary care hospital and (C) transferred with CT or MRI scans. The transfer time of each group were compared and analyzed statistically. Additionally, the number and type of imaging performed at the primary care hospital were analyzed. Results: All qualified patients (n=276) were enrolled in this study: 121 patients in group A; 104 in group B;51 in group C. There was a statistically significant difference in the transfer time between the three groups (pvalue<0.001), and 79 (28.6%) were transferred to an emergency medical center within one hour. In group C,CT or MRI scans were performed an average of 1.86 times at the primary care hospital, and the median transfer time was 4 hours 5 minutes. Conclusion: Only 28.6% of the cases in the study arrived within the golden hour at a definitive care facility. Such delays are in part the result of prolonged times at the primary care hospital for radiologic examinations,such as CT or MRI scans. Major multiple trauma patients should be transferred to a definitive care facility directly or as soon as the primary survey and the resuscitation of Advanced Trauma Life Support guideline are completed at the primary care hospital. (J Korean Soc Traumatol 2011;24:25-30) KCI Citation Count: 22